IMPLICATIONS OF ISLAMIC EDUCATION PERSPECTIVE OF IBNU KHALDUN IN ELEMENTARY SCHOOLS - Buny Andaru Bahy, Moh.; Akhmad Taufiq, Mirwan (Al-Mudarris: Journal Of Education, 2023)
Education is the most important element in human life because education has the aim of making future generations superior and competitive. The application of the concept of Islamic education philosophy in education aims to make an ideal and structured education to achieve learning objectives. Several concepts of Islamic education philosophy have been developed by scholars, one of which was the concept that Ibn Khaldun coined. This study aims to determine the implementation and influence of Islamic education philosophy according to Ibnu Khaldun at Khairunnas Elementary School Surabaya. Researchers used qualitative research methods with a descriptive qualitative approach. This type of research in this analysis uses field studies. The results of this study state that the Khairunnas Elementary School Surabaya has implemented the concept of Islamic education philosophy from Ibn Khaldun's perspective. It can be seen by applying Ibn Khaldun's four concepts: curriculum, educators, students, and teaching methods. Applying these four concepts can have a good influence on all elements of education at Khairunnas Surabaya Elementary School, both from the elements of the curriculum, educators, students, and the application of teaching methods.